Increased TRPC6 expression is associated with tubular epithelial cell proliferation and inflammation in diabetic nephropathy. (February 2018) - Fu, Yanqin; Wang, Chongxian; Zhang, Dongming; Xin, Yaping; Li, Jun; Zhang, Yuanyuan; Chu, Xiaojing
Highlights: TRPC6 expression level significantly upregulate in DN patient tissues and HK-2 cells. Ectopic expression of TRPC6 protein directly affects TECs proliferation and apoptosis. Ectopic expression of TRPC6 protein affects inflammatory cytokines release in TECs. Over-expression of TRPC6 inhibition of the NFAT signaling pathway. TRPC6 modulates TECs cell growth and apoptosis by targeting the NFAT signaling pathway. Abstract: Although TRPC6 expression is shown to be significantly elevated in a rat model diabetic nephropathy (DN), its expression and role in human DN are unclear. We thus explored the role of TRPC6 in the pathophysiology of tubular epithelial cell injury following DN. HK-2 cells were cultured in a high-glucose medium to induce a DN cell model. Ad-TRPC6 and TRP6 siRNA were transfected to overexpress and knock down TRPC6. We found that TRPC6 expression was significantly upregulated in DN tissues and cells. TRPC6 siRNA inhibited cell proliferation and promoted cell apoptosis in HK-2 cells treated with high glucose, whereas Ad-TRPC6 showed the opposite effect. Furthermore, Ad-TRPC6 significantly promoted release of IL-8 and IL-6. Subsequent experiments demonstrated that the signaling pathway of nuclear factor of activated T cells (NFAT) was activated by Ad-TRPC6 and deactivated by TRPC6 siRNA. The NFAT signaling inhibitor, FK-506, eliminated the effect of TRPC6 on HK-2 cells. These results suggest that TRPC6 was upregulated in DN and could promote cell proliferation and inflammation by inhibiting the NFAT signaling pathway in tubular epithelial cells.